Two-Step Thermochemical Cellulose Hydrolysis With Partial Neutralization for Glucose Production - Kong-Win Chang, James; Duret, Xavier; Berberi, Véronique; Zahedi-Niaki, Hassan; Lavoie, Jean-Michel (Frontiers in Chemistry, 2018)
Cellulose hydrolysis processes using concentrated acid usually involve two steps in order to obtain high glucose yields. The first step (pre-treatment) decrystallizes cellulose while the second step (post-hydrolysis) converts the amorphous cellulose to glucose. The two-step process developed by the Industrial Research Chair on Cellulosic Ethanol and Biocommodities and its industrial partner CRB Innovations Inc., includes an intermediate partial neutralization step, whose purpose is to decrease the amount of dilution water to be added for post-hydrolysis thus minimizing handling costs. In this work, the effect of several operating parameters on the glucose yield of this process was investigated using triticale cellulose and the best conditions yielding fermentable glucose (close to 100%) were determined. These conditions involve pretreating cellulose at 30ºC using 72 wt% H2SO4 with a H2SO4/dry cellulose mass ratio of 36 over 2 h, followed by a partial neutralization using 20 wt% NaOH at an H+/OH- molar ratio of 2.3-2.5 and a post-hydrolysis at 121ºC for 10 min.